The Impact of COVID-19 Pandemic on Teachers’ Creativity of Online Teaching Classrooms in the Saudi EFL Context - Al-khresheh, Mohammad H. (Frontiers in Education, 2022)
The worldwide coronavirus disease (COVID-19) has engendered substantial changes for teachers and students. During this epidemic, teachers have been trying to adapt to unforeseen conditions and teaching in remarkable ways to meet the objectives of their virtual lessons. Accordingly, teachers' creativity has been significantly affected by this severe condition. Therefore, this study aimed to explore to what extent teachers were able to enhance creativity in their classes during the pandemic from their students' perceptions in the Saudi EFL context. Moreover, the study sought to determine whether these perceptions diverged significantly due to students' gender and university level and teachers' gender. To this end, a 62-item English Language Teacher Creativity Scale with seven multi-dimensions constructed by Pishghadam et al. (2012) was carried out on a group of 500 male and female university students chosen by a snowball sampling method. Results from this descriptive quantitative study showed a moderate level of creativity in the teaching styles of EFL teachers. The unexpected pandemic has affected teachers' preparedness and limited their capacity to develop creative online teaching methods. Results have also shown no significant differences between the perceptions of students and the level of their teachers' creativity due to students' gender, university level, and teacher's gender. Based on these results, limitations and recommendations were provided.